Analisis Pengaruh Harga dan Karakteristik Konsumen terhadap Keputusan Pembelian pada Data.Com Computer Kota Pangkal Pinang - Sumar - (Jurnal Bisnis Darmajaya, 2015)
This research aims to investigate and examine the influence of price and consumer characteristics toward the purchasing decision at Data.Com Computer Kota Pangkalpinang.This research is a descriptive and quantitative research. The method of sampling used in this research is the nonprobability sampling, particularly the accidental sampling. The population of this study is the consumer of Data.Com Computer Kota Pangkalpinang. The samples of this study are 138 people who are taken by using Sevilla Slovin formula with 5% error margin. The data analysis was conducted through descriptive statistics, validity test, reliability test, classical assumption test, t-test, F-test, multiple regression analysis and determination coefficient (R2).            The result of the research shows that partially the price variable has 1.182 positive effect with t-test of 23.679 1.65 t-table at significance level of 0.000 0.05 toward the purchasing decision, and consumer characteristic variable has 0.037 positive effect with t-test of 5.650 1.65 t-table at significance level of 0.000 0.05 toward the purchasing decision. Simultaneously, the price variable and consumer characteristic have positive and significant effect toward the purchasing decision with F-test of 1070.838 3.06 F-table at significance level of 0.000 0.05. The adjusted R-square is 0.940 which means that 94% of purchasing decision can be explained or influenced by the price and consumer characteristic variables, while the remaining 6% of purchasing decision are influenced by other variables which are not studied in this research.  Key words –price, consumer characteristics, purchasing decision.